Ḥifẓullisān, maʻrūf bah, Ḵẖāliq-i bārī - Z̤iyāʼuddīn Ḵẖusrau, 17th cent (Silsilah-yi mat̤būʻāt-i Anjuman Taraqqī-yi Urdū, Hind, 1944)
Critical edition of a 17th century verse work written to teach Hindi to Persian speaking people in India.